2008
DOI: 10.1016/j.intcom.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Explaining B2C e-commerce acceptance: An integrative model based on the framework by Gatignon and Robertson

Abstract: This study attempts to analyze e-commerce adoption, proposing a global model that integrates the most relevant approaches in the literature. Gatignon and Robertson's Adoption Model is taken as a reference framework because of its overall nature and its agreement with the main theories used to explain e-commerce acceptance. Thus, the model proposed to explain e-commerce adoption by consumers includes the simultaneous influence of attitudes, social norms, perceived risk, personal innovativeness in the field of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 68 publications
5
9
1
Order By: Relevance
“…This means that the BMT management personnel wished to use a system that is compatible to BMT's requirements and can be operated in any system. The findings of this study support those of Crespo and Rodrigues (2008), who indicated that compatibility has a positive significant connection with the usefulness perception to adopt e-commerce. Compatibility was not found to have any direct influence on ease of use perception.…”
Section: System Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…This means that the BMT management personnel wished to use a system that is compatible to BMT's requirements and can be operated in any system. The findings of this study support those of Crespo and Rodrigues (2008), who indicated that compatibility has a positive significant connection with the usefulness perception to adopt e-commerce. Compatibility was not found to have any direct influence on ease of use perception.…”
Section: System Characteristicssupporting
confidence: 88%
“…An individual will tend to use a system if it fulfills job needs. A study conducted by Crespo and Rodrigues (2008) showed that the compatibility has positive and significant connection with the usefulness perception in using e-commerce. Hu, Clark, and Ma (2003) also reported that compatibility has the impact to the perceived ease of use in adopting the technology ( Figure 2).…”
Section: Compatibilitymentioning
confidence: 99%
“…Perceived risk in this research is defined as an uncertainty combination plus seriousness of outcome involved. Since it is difficult to capture and measure its objective reality, perceived risk has been often defined as a relevant specific and situational parameter in different research fields (Yousafzai et al, 2003;Belanger & Carter, 2008;Teo & Liu, 2007;Crespo & Rodríguez, 2008). It could be defined as the possibility that the use of an innovation might not be safe (Gerrard & Cunningham, 2003).…”
Section: Perceived Risk and Usage Intentionmentioning
confidence: 99%
“…Pavlou and Gefen [18] used TPB to identify drives of e-commerce adoption. Similarly, Herrero Crespo and Rodríguez Del Bosque Rodríguez [19] used TPB to examine factors that lead consumers to adopt B2C e-commerce. In addition, Merikivi and Mantymaki [20] used TPB to understand why people continue to use social virtual worlds.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Research shows that the pressure to bend to normative influence increases for actions performed in public, whereas this pressure decreases for actions done in private [30,31]. In recent years, a number of studies [19,32] were conducted to build and validate a model of IT acceptance around a subjective norm, a construct conceptually close to social norms. For example, these studies each presented a model of e-commerce adoption to identify the factors including subjective norm that can predict a buyer's attitude, and then purchase intention.…”
Section: Normative Social Influencementioning
confidence: 99%